Communities of healing practice on al-Baṭinah coast of Oman - Ismail, Hanadi (Proceedings of the Seminar for Arabian Studies, 2013)
This paper investigates the communities of healing on al-Baṭinahh coast of Oman. It reports on the findings of ethnographic research on three types of ceremonies: zār, mikwara, and malid. While zār is one of the more well-researched healing rituals in the field, neither mikwara nor malid have been previously examined. The data reveal differentiation at the levels of typology and structure. Zār has previously been discussed in the literature as a women-only phenomenon, and possession has been viewed as a symbolic expression of resistance by a subordinate group or an act of protest against being excluded from the sacred space. Some of these interpretations were, in addition, flavoured by a western, or Eurocentric, orientation, a trend that has been criticized by a number of anthropologists and ethnographers. Critically, new data presented here show that women and men participate in these events equally. In understanding the phenomenon of possession and spirits as performed in the ceremonies of zār, mikwara, and malid, the author follows a fresh empirical approach in examining the anatomy of possession, practitioners of healing, and participants within the socio-cultural context of al-Baṭinahh, relying on evidence obtained from participant observation, narratives, and interviews.